On the relationship between peer isolation and offending specialization: the role of peers in promoting versatile offending - Thomas, Kyle J. (Crime & delinquency, 2016)
Despite the salient role many criminologists accord peers as a source of influence in the frequency and character of offending, little is known about the role peers play in promoting offending versatility. The current study contributes to this understanding by testing the hypothesis that individuals isolated from peers display greater levels of specialization than their nonisolate counterparts. Using data from the National Youth Survey, the analyses examine (a) the contemporaneous effects of isolation from peers on offending versatility and (b) how changes in isolation status affect changes in offending diversity. Results indicate that peer isolates are more likely to specialize in offending than nonisolates. Moreover, individuals change their level of offending diversity after their status as a peer isolate changes. The discussion considers the implications of these findings and offers avenues for future research.